2014
DOI: 10.2478/s11535-014-0314-1
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Vitis vinifera L. within the Slovak national collection of genetic resources

Abstract: Microsatellites were used as a very effective tool for genetic diversity analysis and characterization of 51 grapevine (Vitis vinifera L.) accessions from the national collection of genetic resources. Genetic diversity was relatively high, 8.91 alleles were detected per analysed microsatellite locus in average, and fifty-one accessions were distinguished into 45 groups. Distribution of recent Slovak cultivars across the dendrogram accented both their genetic diversity and the effectiveness of the national bree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…The PI or the Probability of identity is the probability that two individuals of a population or sample have the same genotype by chance and not by kinship (MIRIMIN et al, 2015). This is the most used theoretical estimator to access the relied statistical for individual identification and to quantify the levels of genetic diversity in populations or samples (WAITS;LUIKART;TABERLET, 2001;DOKUPILOVÁ et al, 2014;MOLLET et al, 2015). According to Hvarleva et al (2007), average PI values higher than 0.546 are associated to a low amount of identified alleles.…”
Section: Resultsmentioning
confidence: 99%
“…The PI or the Probability of identity is the probability that two individuals of a population or sample have the same genotype by chance and not by kinship (MIRIMIN et al, 2015). This is the most used theoretical estimator to access the relied statistical for individual identification and to quantify the levels of genetic diversity in populations or samples (WAITS;LUIKART;TABERLET, 2001;DOKUPILOVÁ et al, 2014;MOLLET et al, 2015). According to Hvarleva et al (2007), average PI values higher than 0.546 are associated to a low amount of identified alleles.…”
Section: Resultsmentioning
confidence: 99%
“…They suggested that the probability of finding two individuals with the same genotype was very close to zero, considering both the marker set and the sample size utilized. However, the PI is considered the most widely used theoretical estimator for accessing supporting statistics for individual identification and quantifying the level of genetic variability in populations or samples ( Dokupilová et al, 2014 ; Mollet et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%